2014
DOI: 10.1186/1472-6882-14-359
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of the sclerotium of Lignosus rhinocerotis (Cooke) Ryvarden, the Tiger Milk mushroom

Abstract: BackgroundThe sclerotium of Lignosus rhinocerotis (Cooke) Ryvarden (Tiger Milk mushroom) is used as a traditional medicine to relieve cough, asthma and chronic hepatitis. The traditional uses of the sclerotium are presumably related to its anti-inflammatory effect. The present study was carried out to evaluate the anti-inflammatory activity of the sclerotial powder of L. rhinocerotis (Cooke) Ryvarden (Tiger Milk mushroom) cultivar TM02.MethodsThe anti-acute inflammatory activity of the sclerotial powder of L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…The cotton pellet-induced granuloma test is a model for studying the transudative and proliferative components of chronic inflammatory processes [26]. After several days of cotton pellet implantation, giant cells and undifferentiated connective tissue can be observed in addition to the fluid infiltration histologically.…”
Section: Discussionmentioning
confidence: 99%
“…The cotton pellet-induced granuloma test is a model for studying the transudative and proliferative components of chronic inflammatory processes [26]. After several days of cotton pellet implantation, giant cells and undifferentiated connective tissue can be observed in addition to the fluid infiltration histologically.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to treat gastric ulcers, chronic hepatitis and liver cancer ( Wong and Cheung, 2009 ). Previous studies demonstrated that the sclerotia of L. rhinocerotis exhibit anti-proliferative, anti-oxidant, anti-microbial, anti-inflammatory, and immunomodulatory effect as well as stimulatory effect on neurite outgrowth ( Lai et al, 2008 ; Wong et al, 2009 , 2011 ; Eik et al, 2012 ; Lee et al, 2012 ; Mohanarji et al, 2012 ; Lau et al, 2013 ; Phan et al, 2013 ; Yap et al, 2013 ; Zaila et al, 2013 ; Lee et al, 2014 ). Non-digestible carbohydrates (NDCs) from the sclerotia may function as novel prebiotics ( Gao et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The recent domestication of the mushroom has enabled assessment of the mushroom for antiproliferation activity against cancer cells, as well as its immunomodulatory, antioxidant, anti-inflammatory, antimicrobial, and neuritogenic activities. [8][9][10][11][12][13] The cultivated sclerotial powder at daily oral dose of up to 1,000 mg/kg was found to show no adverse effect on the growth rate, hematological and clinical biochemical parameters (including renal and liver function parameters) in animal studies. No pathological changes were found in the liver, kidney, heart, spleen, and lung of the treated animals.…”
Section: Introductionmentioning
confidence: 99%